2017
DOI: 10.1111/jocn.13867
|View full text |Cite
|
Sign up to set email alerts
|

A willingness to go there: Nurses and spiritual care

Abstract: There is a dire need to prepare undergraduate and graduate students to assess and support a patient's spiritual needs. Addressing spiritual care content as a clinical and educational priority will promote a patient-centred approach for spiritual care and can further shape nursing curricula, policies, guidelines and assessment tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 42 publications
0
49
0
4
Order By: Relevance
“…The literature shows that more SC training for nurses is needed. Such education could improve nurses' sensitivity to spirituality and enhance the integration of SC within clinical practice and patient's health and satisfaction with care [52, [55][56][57][58][59]. We believe that attention to the patients' spirituality by nurses could be made more consistent by training nurses in using both proactive and 'nonactive' modes, in addition to the reactive mode.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…The literature shows that more SC training for nurses is needed. Such education could improve nurses' sensitivity to spirituality and enhance the integration of SC within clinical practice and patient's health and satisfaction with care [52, [55][56][57][58][59]. We believe that attention to the patients' spirituality by nurses could be made more consistent by training nurses in using both proactive and 'nonactive' modes, in addition to the reactive mode.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…As alluded to above, in this space, chaplains are free to be present. Minton et al (2017) describe presence as a function of 'sentience' and 'sagacious insight'. According to Minton et al, sentience is beyond cognition and everyday perception.…”
Section: Discussionmentioning
confidence: 99%
“…National guidelines and extensive literature support the importance of spiritual screening and assessment by clinicians and chaplains, but studies have demonstrated deficiencies in this area 4,7‐14 . The National Consensus Project (NCP) Guidelines for Quality Palliative Care recommend routine spiritual screening by clinicians and availability of spiritual care providers such as chaplains for more comprehensive assessment and spiritual support 1 .…”
Section: Introductionmentioning
confidence: 99%